Mutual acoustic identification in the swarm of e-puck robots. (27th June 2017) - Nemec, Dušan; Janota, Aleš; Hruboš, Marián; Gregor, Michal; Pirník, Rastislav
This article analyses and mathematically describes a method for mutual identification of multiple mobile robots. The method interchanges identification numbers among multiple robots via audible beeps multiplexed by frequency. The identification sound is sent only when robots approach to each other. The algorithm was primary designed for e-puck robots, but it can be used in any multi-agent robotic system; each mobile robot has to be equipped with three microphones for determination of the sound's direction, speaker and signal processing microcontroller.